Research on scheduling method based on traffic matrix for IoT security. Issue 2 (11th February 2020) - Cao, Shaohua; Zhu, Dongjie; Li, Guofu; Zhang, Yanwu; Fan, Xiani; Geng, Shanshan; Du, Haiwen; Cao, Ning
Summary: With the increasing number of sensors in the Internet of Things (IoT), network nodes are prone to load imbalance, which seriously affects the reliability and scalability of the IoT. In this paper, a method of load balancing is proposed to reduce the pressure of switches in IoT and improve the efficiency of switch. The method is based on software defined network (SDN) technology using dynamic traffic scheduling of server cluster (DTSSC) model. It obtains the traffic and load matrices for each server and achieves load balancing on each of them. This method has high efficiency and low overhead and is easy to deploy. The validity of this method is verified through experiments; ie, the load ratio of each server is balanced. Abstract : In this paper, a method of load balancing is proposed to reduce the pressure of switches in IoT and improve the efficiency of switch. The method is based on software defined network (SDN) technology using dynamic traffic scheduling of server cluster (DTSSC) model. It obtains the traffic and load matrices for each server and achieves load balancing on each of them. This method has high efficiency and low overhead and is easy to deploy.